A study on consumer’s purchase intention among millenials towards smartphones brand from China in Malacca / Abdul Azim Jamaluddin - Jamaluddin, Abdul Azim (Faculty of Business and Management, 2019)
The title for this research study is “A Study on Consumer Purchase Intention towards Smartphone Brand from China among Millenials in Malacca”. The main objective for this research is to examine the relationship between price, perceived quality, brand awareness, perceived feature towards purchase intention of smartphone brand from China in Malacca. Thus there is four independent variables are identified, that influence purchase intention of smartphone brand from China, which are price, perceived quality, brand awareness and perceived feature. In order to complete the research, four hypothesis were constructed, focusing on the determining the influence of the independent variables towards dependent variables. A total of 120 respondent had participated are randomly chosen, using non-probability sampling which is convenience method. This study used primary data collection namely questionnaire and using online method for easier way of data collection method. The data obtain then were analysed using SPSS to determine the reliability test, Pearson Correlation coefficient, and regression testing. The finding shows that all the independent variable have significantly influence purchase intention of smartphone brand from China. Thus, all the hypothesis developed are accepted.